Cost-Effective Transcriptome-Wide Profiling of Circular RNAs by the Improved-tdMDA-NGS Method - Guria, Ashirbad; Sharma, Priyanka; Srikakulam, Nagesh; Baby, Akhil; Natesan, Sankar; Pandi, Gopal (Frontiers in Molecular Biosciences, 2022)
Covalently closed circular RNAs are neoteric to the eukaryotic family of long non-coding RNAs emerging as a result of 5’-3’ backsplicing from exonic, intronic or intergenic regions of the parental RNA transcript. Owing to its unique structure and stability, circular RNA has gained multitude functional aspects such as biomarkers, microRNA and protein sponges, direct and indirect modulator of gene expression, protein translation and many unproven activities. However, due to its low abundance, most of the global circular RNA identification is carried out by high-throughput NGS based approaches requiring millions of sequencing reads. This lag in methodological advancements demands for newer, more refined and efficient identification techniques. Here, we aim to show an improved version of our previously reported template dependent multiple displacement amplification (tdMDA)-NGS method by superimposing the ribosomal depletion step and use of H minus reverse transcriptase and RNase H. Implication of tdMDA using highly replicative Phi29 DNA polymerase after minimising the linear and ribosomal RNA content further intensifies its detection limit towards even the abysmally expressing circular RNA at a low NGS depth, thereby decreasing the cost of identifying a single circular RNA. A >11-fold and >6-fold increase in total circular RNA was identified from improved-tdMDA-NGS method over traditional method of circRNA sequencing using DCC and CIRI2 pipelines respectively from Oryza sativa sp. Indica. Furthermore, the reliability of the improved-tdMDA-NGS method was also asserted in HeLa cell line showing significant fold difference in comparison with the existing traditional method of circRNA sequencing. Among the identified circular RNAs, a significant percentage from both rice (~58 %) and HeLa cell lines (~84 %) are found to be matched with the previously reported circular RNAs, suggesting the improved-tdMDA-NGS method can be adapted to detect and characterise the circular RNAs from different biological systems.